2015
DOI: 10.1007/s10689-015-9779-y
|View full text |Cite
|
Sign up to set email alerts
|

The breast cancer immunophenotype of TP53-p.R337H carriers is different from that observed among other pathogenic TP53 mutation carriers

Abstract: Germline TP53 mutations are associated with Li-Fraumeni syndrome, an autosomal dominant disorder characterized by a predisposition to multiple early-onset cancers including breast cancer (BC), the most prevalent tumor among women. The majority of germline TP53 mutations are clustered within the DNA-binding domain of the gene, disrupting the structure and function of the protein. A specific germline mutation in the tetramerization domain of p53, p.R337H, was reported at a high frequency in Southern and Southeas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…34 However, a Brazilian study of 78 patients with breast cancer demonstrated that the median age at breast cancer diagnosis in a group of p.R337H carriers (n = 66) was 42 years, which was older than the median age at diagnosis (30 years) for carriers of other nonfunctional germline TP53 mutations. 35 In addition, most patients had a positive hormone receptor status, and in contrast to other studies, HER2+ breast cancer was very similar to that observed in noncarriers of TP53 variants. 35 Numerous sarcoma types collectively constitute less than 1% of all cancers and often occur sporadically.…”
Section: Cancer November 1 2020mentioning
confidence: 46%
See 3 more Smart Citations
“…34 However, a Brazilian study of 78 patients with breast cancer demonstrated that the median age at breast cancer diagnosis in a group of p.R337H carriers (n = 66) was 42 years, which was older than the median age at diagnosis (30 years) for carriers of other nonfunctional germline TP53 mutations. 35 In addition, most patients had a positive hormone receptor status, and in contrast to other studies, HER2+ breast cancer was very similar to that observed in noncarriers of TP53 variants. 35 Numerous sarcoma types collectively constitute less than 1% of all cancers and often occur sporadically.…”
Section: Cancer November 1 2020mentioning
confidence: 46%
“…35 In addition, most patients had a positive hormone receptor status, and in contrast to other studies, HER2+ breast cancer was very similar to that observed in noncarriers of TP53 variants. 35 Numerous sarcoma types collectively constitute less than 1% of all cancers and often occur sporadically. However, sarcomas represent 17.4% of all cancers in TP53 germline mutation carriers and 36.8% of all cancers in patients younger than 20 years.…”
Section: Cancer November 1 2020mentioning
confidence: 46%
See 2 more Smart Citations
“…The detection rate may be especially increased in women with HER2+ breast tumors, although this is based only on one study. Interestingly, there is published evidence that patients with the reduced penetrance Brazilian founder pathogenic variant c.1010G>A (p.Arg337His) are less likely to develop HER2+ breast tumors than other TP53 carriers (Fitarelli‐Kiehl et al., ), inferring that HER2‐positive tumor status may be less predictive for p.Arg337His and potentially other reduced penetrance variants.…”
Section: Discussionmentioning
confidence: 99%